The versatility of the Helicobacter pylori vacuolating cytotoxin VacA in signal transduction and molecular crosstalk - Backert, Steffen; Tegtmeyer, Nicole (Toxins, 2010)
By modulating important properties of eukaryotic cells, many bacterial protein toxins highjack host signalling pathways to create a suitable niche for the pathogen to colonize and persist. Helicobacter pylori VacA is paradigm of pore-forming toxins which contributes to the pathogenesis of peptic ulceration. Several cellular receptors have been described for VacA, which exert different effects on epithelial and immune cells. The crystal structure of VacA p55 subunit might be important for elucidating details of receptor interaction and pore formation. Here we discuss the multiple signalling activities of this important toxin and the molecular crosstalk between VacA and other virulence factors. © 2010 by the authors; licensee Molecular Diversity Preservation International, Basel, Switzerland.
Created from Fastlane, Scopus look-up
Keywords: CagA; Helicobacter pylori; Lipid rafts; Pathogenicity island; Signalling; Type IV secretion; VacA; Vacuolating cytotoxin